TH2.2: A Guide for Conducting Ethical Gender-Inclusive Research: The Gender Research Ethics and Standards Toolkit - Faas, Simone; Makhija, Simrin; Bryan, Elizabeth; Go, Ara; Malapit, Hazel J. (CGIAR GENDER Impact Platform, 2022)
As gender-inclusive designs assume a more central place in research related to food, land, and water systems and donors now routinely require a gender-sensitive lens on research, there is a heightened demand among researchers for a comprehensive resource on the ethical considerations involved in gender research. In response to this growing demand, the CGIAR GENDER Impact Platform's Methods Module team has developed a toolkit, titled "Gender Research: An Ethics and Standards Toolkit." This toolkit is aligned with the CGIAR Ethics Framework and the CGIAR Research Ethics Code and it is intended to serve as a reference guide for researchers within CGIAR and beyond. It provides guidance, recommendations, and resources on gender-relevant ethical considerations, as well as additional gender considerations regarding the ethical treatment and protection of human subjects that are applicable to different types of research. The resources and guidance in the toolkit span various stages of a project's lifetime, including project development and design, building research partnerships, project implementation and fieldwork, and data analysis, storage, and dissemination. It also includes a practical checklist for research design, data collection, and data storage. Importantly, this toolkit is designed as a "living" document which will be periodically updated to reflect new resources and include additional topics of interest.